2003
DOI: 10.1002/art.11359
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic antiphospholipid syndrome: Where do we stand?

Abstract: Micrometer‐sized monodispersed mesoporous silica spheres with adjustable particle diameter and adjustable pore structure were successfully prepared. Drops of a silica sol were injected by a microfluidic device into a heated oil bath where the droplets solidified during sedimentation. Drop size was varied by control of the rates of the oil flow past the silica sol injector. The silica sol was made by prehydrolysis of tetraethyl orthosilicate (TEOS) in an aqueous acidic solution using a triblock copolymer as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 76 publications
(85 reference statements)
0
50
0
1
Order By: Relevance
“…The prevalence of "aPL-nephropathy" in SLE patients without aPL varies between 4%-16 %, whereas 25%-39% of the aPL-positive SLE patients have "aPL-nephropathy" (92,94 Catastrophic antiphospholipid syndrome Encountered in less than 1% of APS patients, catastrophic APS is characterized by accelerated widespread small/medium vessel thromboses with unusual organ involvement and has a mortality of 30%-50% despite aggressive multimodal intensive treatment (102)(103)(104).…”
Section: Renal Impairmentmentioning
confidence: 99%
“…The prevalence of "aPL-nephropathy" in SLE patients without aPL varies between 4%-16 %, whereas 25%-39% of the aPL-positive SLE patients have "aPL-nephropathy" (92,94 Catastrophic antiphospholipid syndrome Encountered in less than 1% of APS patients, catastrophic APS is characterized by accelerated widespread small/medium vessel thromboses with unusual organ involvement and has a mortality of 30%-50% despite aggressive multimodal intensive treatment (102)(103)(104).…”
Section: Renal Impairmentmentioning
confidence: 99%
“…Definite criteria for CAPS diagnosis include (i) the involvement of at least three organs, systems or tissues, (ii) development of clinical manifestations at the same time or within 1 week, (iii) confirmation by histopathology of small-vessel occlusion and (iv) laboratory criteria for APS [96][97][98]. Despite the low incidence of CAPS (<1%), it is a life-threatening medical condition with a case fatality rate of 50%.…”
Section: Treatment Of Capsmentioning
confidence: 99%
“…120 Due to the rarity or catastrophic APS, RCTs are not available to guide treatment. Investigators have reported several interventions that may be of benefit [119][120][121] and are used by us to guide treatment of these patients. The cornerstone of treatment appears to be the prompt use of anticoagulation (in the absence of concurrent hemorrhage) and the identification and treatment of possible underlying infection.…”
Section: Catastrophic Apsmentioning
confidence: 99%